Evaluation of Children and Adolescent Cases Admitted to the Pediatric Emergency Department for Drug Intoxication - İsmail Dündar; Yasemin Akın; Melek Yücel; Dündar Yaykıran (Galenos Yayinevi, 2021)
Introduction:Drug poisoning in childhood is one of the leading preventable health problems worldwide. This study aimed to evaluate the epidemiological characteristics, factors facilitating poisoning, and post-poisoning follow-up of the patients who applied to our emergency department with drug intoxication.Methods:Between January 2010 and August 2011, of the total number of 894 patients applying with drug intoxication to the Pediatric Emergency Clinic of the University of Health Sciences Turkey, Kartal Dr. Lütfi Kırdar Training and Research Hospital, 314 patients who gave consent were included in the study. The patients were evaluated retrospectively.Results:Of the 894 patients presenting with drug intoxication, results for 314 patients with consent were evaluated. The mean age of the 314 cases was 4.6±4.0 years. The sex distribution was 138 girls (43.9%) and 176 boys (56.1%). The mean age was 5.7±4.8 years for girls and 3.8±3.1 years for boys. In the preschool period (0-5 years) and age group of 5-10 years, boys were predominant, while at the age group of 10-14 years, girls were at the forefront. While the most common drug group causing poisoning was central nervous system drugs, analgesic-antipyretic drugs took the second place. During adolescence, drug intoxications with suicidal intentions were especially prominent.Conclusion:As in all over the world, drug intoxication cases are one of the most important preventable emergency causes in Turkey. The most common cause of childhood intoxication is accidental, it is seen more in boys in the preschool and school-age, and it occurs mostly in the 0-5 age group. Girls are more affected at adolescence. During adolescence, intoxications with suicidal intentions are common. Thus, poisonings during this period should be evaluated from a psychiatric point of view.